2019
DOI: 10.1002/pon.5087
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction among older adult, long‐term cancer survivors: A comparison of Black with White survivors

Abstract: Objective This paper proposes and evaluates a model of the relative importance that cancer‐related health factor along with other health factors have for the self‐rated health and life satisfaction of older adult, long‐term cancer survivors. The data are examined in the context of important racial differences in health and life satisfaction along with other covariates including gender and education. Method This research utilizes regression‐based path analysis to examine data from a sample of 321 older (age 60+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
0
11
1
1
Order By: Relevance
“…• Certains symptômes indésirables peuvent perturber les fonctions physiques et les activités quotidiennes du survivant, ce qu'il perçoit comme une diminution de son bien-être physique (Deimling et al, 2019;Sheikh-Wu et al, 2021). • Durant la phase aiguë de survie, la majorité des symptômes signalés sont physiques, comme la douleur, la fatigue, l'incontinence, la faiblesse généralisée, la neuropathie des mains et des pieds ou encore les nausées et les vomissements (ACS, 2018b).…”
Section: Bien-êtreunclassified
“…• Certains symptômes indésirables peuvent perturber les fonctions physiques et les activités quotidiennes du survivant, ce qu'il perçoit comme une diminution de son bien-être physique (Deimling et al, 2019;Sheikh-Wu et al, 2021). • Durant la phase aiguë de survie, la majorité des symptômes signalés sont physiques, comme la douleur, la fatigue, l'incontinence, la faiblesse généralisée, la neuropathie des mains et des pieds ou encore les nausées et les vomissements (ACS, 2018b).…”
Section: Bien-êtreunclassified
“…LS is what everyone desires since it is an important element of living a happy life [24]. LS occurs as a result of an overall assessment process.…”
Section: Related Literaturementioning
confidence: 99%
“…Reports of QOL under treatment and life satisfaction of older cancer survivors [ 14 ] revealed that, among survivors aged 60 years and older, social support from friends and family is a predictive factor for social well-being [ 15 ]. Furthermore, health-related QOL for cancer survivors and their spouses or partners has been shown to affect satisfaction with cancer treatment outcomes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%